Late-Holocene sediment dynamics and contaminants in the Fecht River, Vosges Mountains, France: From medieval mining to modern floodplains - Charlotte E. Engelmann; Frank Preusser; Alexander Fülling; Gilles Rixhon; Damien Ertlen; Kristin Steger; Raphael Longoni; Isa-Yael Roth; Jan H. Blöthe (CATENA, 2026)

Between evidence and allegation: factual accuracy in discussions on fluoride toxicity and research integrity - Andrea Buettner; Patrick Diel; Gerhard Eisenbrand; Bernd Epe; Petra Först; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; Michael Hellwig; Hans-Ulrich Humpf; Henry Jäger; et al. (Archives of Toxicology, 2026)

Structural basis of HydBC modularity and its diversity in anaerobic bacteria - Anuj Kumar; Jennifer Roth; Lena Schmück; Volker Müller; Jan Schuller (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Elucidating the redox-driven sodium pumping mechanism of the ancient Rnf complex - Hyunho Kim; Anuj Kumar; Patricia Saura; Jennifer Roth; Stefan Bohn; Tristan Reif-Trauttmansdorff; Anja Schubert; Volker Müller; Jan M. Schuller; Ville R.I. Kaila (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Cefepime versus carbapenems for treatment of AmpC beta-lactamase-producing Enterobacterales bloodstream infections - Julia Herrmann; Anne-Valérie Burgener-Gasser; Daniel Goldenberger; Jan Roth; Maja Weisser; Pranita D. Tamma; Sarah Tschudin-Sutter (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose Cefepime is recommended for treating infections caused by AmpC beta-lactamase-producing Enterobacterales (AmpC-PE), though supporting evidence is limited. Therefore, this study compared outcomes associated with cefepime versus carbapenem therapy for bloodstream infections (BSIs) caused by AmpC-PE after phenotypic exclusion of ESBL-co-producing isolates. Methods This retrospective cohort study compared definite cefepime versus carbapenem treatment for AmpC-PE BSI in hospitalized patients of the University Hospital Basel, Switzerland, between 01/2015 and 07/2020. Primary outcomes included in-hospital death, renal impairment and neurologic adverse events; secondary outcomes included length of hospital stay and recurrent infection. Results Two hundred and seventy episodes of AmpC-PE BSI were included, 162, 77 and 31 were treated with a carbapenem, cefepime and other antibiotics, respectively. Patients treated with carbapenems were more likely to be transferred to the ICU on admission and more frequently had central venous catheter as a source of infection. In uni- and multivariable analyses, primary and secondary outcomes did not differ between the two treatment groups, except for more frequent occurrence of neurological adverse events among patients treated with carbapenems and shorter length of hospital stay among survivors treated with cefepime. Conclusion After excluding isolates with phenotypic ESBL-co-production, cefepime was not associated with adverse outcomes compared to carbapenems when used to treat BSIs caused by AmpC-PE. Our study provides evidence to support the use of cefepime as a safe treatment strategy for AmpC-PE BSI, particularly in clinically stable patients without initial renal impairment or increased susceptibility to neurological adverse events.

Basic concepts of mixture toxicity and relevance for risk evaluation and regulation - Denise Bloch; Patrick Diel; Bernd Epe; Michael Hellwig; Alfonso Lampen; Angela Mally; Doris Marko; María A. Villar Fernández; Sabine Guth; Angelika Roth; Rosemarie Marchan; Ahmed Ghallab; et al. (Archives of Toxicology, 2023)
Exposure to multiple substances is a challenge for risk evaluation. Currently, there is an ongoing debate if generic “mixture assessment/allocation factors” (MAF) should be introduced to increase public health protection. Here, we explore concepts of mixture toxicity and the potential influence of mixture regulation concepts for human health protection. Based on this analysis, we provide recommendations for research and risk assessment. One of the concepts of mixture toxicity is additivity. Substances may act additively by affecting the same molecular mechanism within a common target cell, for example, dioxin-like substances. In a second concept, an “enhancer substance” may act by increasing the target site concentration and aggravating the adverse effect of a “driver substance”. For both concepts, adequate risk management of individual substances can reliably prevent adverse effects to humans. Furthermore, we discuss the hypothesis that the large number of substances to which humans are exposed at very low and individually safe doses may interact to cause adverse effects. This commentary identifies knowledge gaps, such as the lack of a comprehensive overview of substances regulated under different silos, including food, environmentally and occupationally relevant substances, the absence of reliable human exposure data and the missing accessibility of ratios of current human exposure to threshold values, which are considered safe for individual substances. Moreover, a comprehensive overview of the molecular mechanisms and most susceptible target cells is required. We conclude that, currently, there is no scientific evidence supporting the need for a generic MAF. Rather, we recommend taking more specific measures, which focus on compounds with relatively small ratios between human exposure and doses, at which adverse effects can be expected.

Effect of erythrophagocytosis-induced ferroptosis during angiogenesis in atherosclerotic plaques - Pauline Puylaert; Lynn Roth; Melissa Van Praet; Isabel Pintelon; Catalina Dumitrascu; Alexander van Nuijs; Greta Klejborowska; Pieter-Jan Guns; Tom Vanden Berghe; Koen Augustyns; Guido R. Y. De Meyer; Wim Martinet (Angiogenesis, 2023)
Intraplaque (IP) angiogenesis is a key feature of advanced atherosclerotic plaques. Because IP vessels are fragile and leaky, erythrocytes are released and phagocytosed by macrophages (erythrophagocytosis), which leads to high intracellular iron content, lipid peroxidation and cell death. In vitro experiments showed that erythrophagocytosis by macrophages induced non-canonical ferroptosis, an emerging type of regulated necrosis that may contribute to plaque destabilization. Erythrophagocytosis-induced ferroptosis was accompanied by increased expression of heme-oxygenase 1 and ferritin, and could be blocked by co-treatment with third generation ferroptosis inhibitor UAMC-3203. Both heme-oxygenase 1 and ferritin were also expressed in erythrocyte-rich regions of carotid plaques from ApoE −/− Fbn1 C1039G+/− mice, a model of advanced atherosclerosis with IP angiogenesis. The effect of UAMC-3203 (12.35 mg/kg/day) on atherosclerosis was evaluated in ApoE −/− Fbn1 C1039G+/− mice fed a western-type diet (WD) for 12 weeks (n = 13 mice/group) or 20 weeks (n = 16–21 mice/group) to distinguish between plaques without and with established IP angiogenesis, respectively. A significant decrease in carotid plaque thickness was observed after 20 weeks WD (87 ± 19 μm vs. 166 ± 20 μm, p = 0.006), particularly in plaques with confirmed IP angiogenesis or hemorrhage (108 ± 35 μm vs. 322 ± 40 μm, p = 0.004). This effect was accompanied by decreased IP heme-oxygenase 1 and ferritin expression. UAMC-3203 did not affect carotid plaques after 12 weeks WD or plaques in the aorta, which typically do not develop IP angiogenesis. Altogether, erythrophagocytosis-induced ferroptosis during IP angiogenesis leads to larger atherosclerotic plaques, an effect that can be prevented by ferroptosis inhibitor UAMC-3203.

Seawater desalination by forward-osmosis-assisted temperature swing solvent extraction - Jan Frauholz; Hannah Roth; Matthias Wessling (Desalination, 2023)

The cumulative impacts of droughts and N deposition on Norway spruce (Picea abies) in Switzerland based on 37 years of forest monitoring - Simon Tresch; Tobias Roth; Christian Schindler; Sven-Eric Hopf; Jan Remund; Sabine Braun (Science of The Total Environment, 2023)

Where are we now with European forest multi-taxon biodiversity and where can we head to? - Sabina Burrascano; Francesco Chianucci; Giovanni Trentanovi; Sebastian Kepfer-Rojas; Tommaso Sitzia; Flóra Tinya; Inken Doerfler; Yoan Paillet; Thomas Andrew Nagel; Bozena Mitic; Lourdes Morillas; Silvana Munzi; et al. (Biological Conservation, 2023)

Evaluation of the genotoxic potential of acrylamide: Arguments for the derivation of a tolerable daily intake (TDI value) - Sabine Guth; Matthias Baum; Alexander T. Cartus; Patrick Diel; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Dirk Haller; Volker Heinz; Michael Hellwig; Jan G. Hengstler; et al. (Food and Chemical Toxicology, 2023)

Stellungnahme zu Acetaldehyd als Aromastoff: Aspekte der Risikobewertung - Jan G. Hengstler; Matthias Baum; Alexander T. Cartus; Patrick Diel; Gerhard Eisenbrand; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; et al. (Journal of Consumer Protection and Food Safety, 2022)
Opinion on acetaldehyde as a flavouring substance: considerations for risk assessment Acetaldehyde occurs naturally in many foods and is also used as a flavouring due to its fruity aroma. The International Agency for Research on Cancer (IARC) classified acetaldehyde as possibly carcinogenic to humans and, in combination with oral intake via alcoholic beverages, as carcinogenic to humans. Therefore, the question arises whether the use of acetaldehyde as a flavouring agent is still justifiable. The Senate Commission on Food Safety (SKLM) of the German Research Foundation (DFG) reviewed the scientific basis for health risk assessment of the use of acetaldehyde as a flavouring substance and adopted an opinion. Based on the available data, it is at present not possible to conclude if acetaldehyde is genotoxic and mutagenic in vivo after oral exposure. There is also uncertainty regarding the contribution of acetaldehyde as a flavouring substance to the overall exposure to acetaldehyde. Therefore, a science-based assessment on health risk related to the use of acetaldehyde as a flavouring is not possible at present. Considering the genotoxic potential as well as numerous data gaps that need to be closed for a full risk assessment, the SKLM is concerned about the safety of acetaldehyde as a flavouring substance. For reasons of precautionary consumer protection, the SKLM considers that the use of acetaldehyde as a food additive should be re-evaluated.

Salivary nitrate/nitrite and acetaldehyde in humans: potential combination effects in the upper gastrointestinal tract and possible consequences for the in vivo formation of N-nitroso compounds—a hypothesis - Gerhard Eisenbrand; Matthias Baum; Alexander T. Cartus; Patrick Diel; Karl-Heinz Engel; Barbara Engeli; Bernd Epe; Tilman Grune; Sabine Guth; Dirk Haller; Volker Heinz; Michael Hellwig; et al. (Archives of Toxicology, 2022)

Contribution to the ongoing discussion on fluoride toxicity - Sabine Guth; Stephanie Hüser; Angelika Roth; Gisela Degen; Patrick Diel; Karolina Edlund; Gerhard Eisenbrand; Karl-Heinz Engel; Bernd Epe; Tilman Grune; Volker Heinz; Thomas Henle; et al. (Archives of Toxicology, 2021)
Since the addition of fluoride to drinking water in the 1940s, there have been frequent and sometimes heated discussions regarding its benefits and risks. In a recently published review, we addressed the question if current exposure levels in Europe represent a risk to human health. This review was discussed in an editorial asking why we did not calculate benchmark doses (BMD) of fluoride neurotoxicity for humans. Here, we address the question, why it is problematic to calculate BMDs based on the currently available data. Briefly, the conclusions of the available studies are not homogeneous, reporting negative as well as positive results; moreover, the positive studies lack control of confounding factors such as the influence of well-known neurotoxicants. We also discuss the limitations of several further epidemiological studies that did not meet the inclusion criteria of our review. Finally, it is important to not only focus on epidemiological studies. Rather, risk analysis should consider all available data, including epidemiological, animal, as well as in vitro studies. Despite remaining uncertainties, the totality of evidence does not support the notion that fluoride should be considered a human developmental neurotoxicant at current exposure levels in European countries.

Toxicity of fluoride: critical evaluation of evidence for human developmental neurotoxicity in epidemiological studies, animal experiments and in vitro analyses - Sabine Guth; Stephanie Hüser; Angelika Roth; Gisela Degen; Patrick Diel; Karolina Edlund; Gerhard Eisenbrand; Karl-Heinz Engel; Bernd Epe; Tilman Grune; Volker Heinz; Thomas Henle; et al. (Archives of Toxicology, 2020)
Recently, epidemiological studies have suggested that fluoride is a human developmental neurotoxicant that reduces measures of intelligence in children, placing it into the same category as toxic metals (lead, methylmercury, arsenic) and polychlorinated biphenyls. If true, this assessment would be highly relevant considering the widespread fluoridation of drinking water and the worldwide use of fluoride in oral hygiene products such as toothpaste. To gain a deeper understanding of these assertions, we reviewed the levels of human exposure, as well as results from animal experiments, particularly focusing on developmental toxicity, and the molecular mechanisms by which fluoride can cause adverse effects. Moreover, in vitro studies investigating fluoride in neuronal cells and precursor/stem cells were analyzed, and 23 epidemiological studies published since 2012 were considered. The results show that the margin of exposure (MoE) between no observed adverse effect levels (NOAELs) in animal studies and the current adequate intake (AI) of fluoride (50 µg/kg b.w./day) in humans ranges between 50 and 210, depending on the specific animal experiment used as reference. Even for unusually high fluoride exposure levels, an MoE of at least ten was obtained. Furthermore, concentrations of fluoride in human plasma are much lower than fluoride concentrations, causing effects in cell cultures. In contrast, 21 of 23 recent epidemiological studies report an association between high fluoride exposure and reduced intelligence. The discrepancy between experimental and epidemiological evidence may be reconciled with deficiencies inherent in most of these epidemiological studies on a putative association between fluoride and intelligence, especially with respect to adequate consideration of potential confounding factors, e.g., socioeconomic status, residence, breast feeding, low birth weight, maternal intelligence, and exposure to other neurotoxic chemicals. In conclusion, based on the totality of currently available scientific evidence, the present review does not support the presumption that fluoride should be assessed as a human developmental neurotoxicant at the current exposure levels in Europe.

Low-dose photon irradiation alters cell differentiation via activation of hIK channels - Bastian Roth; Christine S. Gibhardt; Patrick Becker; Manuela Gebhardt; Jan Knoop; Claudia Fournier; Anna Moroni; Gerhard Thiel (Pflügers Archiv - European Journal of Physiology, 2015)

Genome and physiology of the ascomycete filamentous fungus X eromyces bisporus , the most xerophilic organism isolated to date - Su‐lin L. Leong; Henrik Lantz; Olga V. Pettersson; Jens C. Frisvad; Ulf Thrane; Hermann J. Heipieper; Jan Dijksterhuis; Manfred Grabherr; Mats Pettersson; Christian Tellgren‐Roth; Johan Schnürer (Environmental Microbiology, 2015)
Summary X eromyces bisporus can grow on sugary substrates down to 0.61, an extremely low water activity. Its genome size is approximately 22 Mb . Gene clusters encoding for secondary metabolites were conspicuously absent; secondary metabolites were not detected experimentally. Thus, in its ‘dry’ but nutrient‐rich environment, X . bisporus appears to have relinquished abilities for combative interactions. Elements to sense/signal osmotic stress, e.g. HogA pathway, were present in X . bisporus . However, transcriptomes at optimal (∼ 0.89) versus low a w (0.68) revealed differential expression of only a few stress‐related genes; among these, certain (not all) steps for glycerol synthesis were upregulated. X eromyces bisporus increased glycerol production during hypo‐ and hyper‐osmotic stress, and much of its wet weight comprised water and rinsable solutes; leaked solutes may form a protective slime. X eromyces bisporus and other food‐borne moulds increased membrane fatty acid saturation as water activity decreased. Such modifications did not appear to be transcriptionally regulated in X . bisporus ; however, genes modulating sterols, phospholipids and the cell wall were differentially expressed. X eromyces bisporus was previously proposed to be a ‘chaophile’, preferring solutes that disorder biomolecular structures. Both X . bisporus and the closely related xerophile, X erochrysium xerophilum , with low membrane unsaturation indices, could represent a phylogenetic cluster of ‘chaophiles’.

Spinocerebellar Ataxias Type 8, 12, and 17 and Dentatorubro-Pallidoluysian Atrophy in Czech Ataxic Patients - Zuzana Musova; Zdenek Sedlacek; Radim Mazanec; Jiri Klempir; Jan Roth; Pavlina Plevova; Martin Vyhnalek; Marta Kopeckova; Ludmila Apltova; Anna Krepelova; Alena Zumrova (The Cerebellum, 2013)

Rs11892031[A] on chromosome 2q37 in an intronic region of the UGT1A locus is associated with urinary bladder cancer risk - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Urinary bladder cancer risk in relation to a single nucleotide polymorphism (rs2854744) in the insulin-like growth factor-binding protein-3 (IGFBP3) gene - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Thermal expansion and high-temperature P21/c–C2/c phase transition in clinopyroxene-type LiFeGe2O6 and comparison to NaFe(Si,Ge)2O6 - Günther J. Redhammer; Fernando Cámara; Matteo Alvaro; Fabrizio Nestola; Gerold Tippelt; Sebastian Prinz; Jan Simons; Georg Roth; Georg Amthauer (Physics and Chemistry of Minerals, 2010)

Rs710521[A] on chromosome 3q28 close to TP63 is associated with increased urinary bladder cancer risk - Marie-Louise Lehmann; Silvia Selinski; Meinolf Blaszkewicz; Michael Orlich; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truss; Holger Gerullis; Thomas Otto; Dimitri Barski; et al. (Archives of Toxicology, 2010)

Water flow and solute transport in furrow-irrigated fields - Fariborz Abbasi; Jan Feyen; Robert L. Roth; Mike Sheedy; M. T. van Genuchten (Irrigation Science, 2003)

The genes of the lysosomal cysteine proteinases cathepsin B, H, L, and S map to different mouse chromosomes - Jan Deussing; Roth Wera; Rommerskirch Winfried; Wiederanders Bernd; Figura von Kurt; Christoph Peters (Mammalian Genome, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)